The effect of mindfulness on online self-presentation, pressure, and addiction on social media - You, Chunhui; Liu, Yang (Frontiers in Psychology, 2022)
As social media has become more imperative in daily life, people pay more attention to self-presentation and impression management on social media, and some have even become psychologically dependent. There is a large group of socially addicted users who continuously strive to improve their online self-presentation. Due to stress and burnout arising from social media addiction, people change their social media behavior. The influence of mindfulness on social behavior cannot be ignored. This study aims to explore coping behaviors and the role of mindfulness for people under social media pressure and social media addiction in China’s special political environment. We found significant differences in self-presentation, social media pressure, and social media addiction among different circles in the Chinese context. Experiments have shown that people’s socially addictive behaviors and abilities to withstand social media pressure are affected by their mindfulness. In addition, the more social media pressure people perceive on social media, the more likely they are to stop using social media and shift to offline interpersonal interactions. However, when there are more offline interpersonal interactions, people’s willingness to return to social media platforms increases.